Anti-TNF therapy is associated with a reduction in radiation exposure in patients with Crohn's disease. Issue 1 (January 2015) - Aggarwal, Divya; Limdi, Jimmy K.
<x xml:space="preserve">Abstract</x> Objective Patients with Crohn's disease (CD) are often exposed to ionizing diagnostic radiation with inherent risks from protracted exposure. Meanwhile, bolder definitions of disease control have changed treatment paradigms, with earlier introduction of biological therapy in many. Our aim was to compare the effective radiation dose a year before and 1 and 3 years after initiating anti-tumor necrosis factor (anti-TNF) or corticosteroid therapy. Materials and methods We performed a retrospective review of CD patients treated with anti-TNF (infliximab or adalimumab) or corticosteroids at our institution from 2005 to 2012. Results We analyzed 170 patients with CD (114 treated with anti-TNF and 56 treated with corticosteroid). Between the year preceding and the year following therapy, a significant decrease in the mean number of radiology studies (−2.0 vs. −0.2, P=0.001) and the cumulative radiation dose (−3.1 vs. +0.3 mSv, P=0.01) was seen in the anti-TNF group when compared with the steroid group. Between the year preceding therapy and 3 years following therapy, a significant increase in the mean number of radiology studies (+2.3 vs. +0.3, P=0.003) and the cumulative radiation dose (+6.8 vs. +1.3 mSv, P=0.003) was seen in the steroid group when compared with the anti-TNF group. After adjusting for predictors of high diagnostic radiation exposure, the anti-TNF-treated group had a decrease in the number of imaging studies by 2 within a year of therapy (P<0.001). Conclusion Anti-TNF but not corticosteroid therapy is associated with a significant reduction in diagnostic radiation exposure a year after treatment, which persisted after 3 years.